Impact of COVID‐19 on thrombus composition and response to thrombolysis: Insights from a monocentric cohort population of COVID‐19 patients with acute ischemic stroke. (30th January 2022) - Desilles, Jean‐Philippe; Solo Nomenjanahary, Mialitiana; Consoli, Arturo; Ollivier, Véronique; Faille, Dorothée; Bourrienne, Marie‐Charlotte; Hamdani, Mylène; Dupont, Sébastien; Di Meglio, Lucas; Escalard, Simon; Maier, Benjamin; Blanc, Raphael; et al.
Abstract: Background: Resistance to fibrinolysis, levels of procoagulant/antifibrinolytic neutrophil extracellular traps (NETs), and the severity of acute ischemic stroke (AIS) are increased by COVID‐19. Whether NETs are components of AIS thrombi from COVID‐19 patients and whether COVID‐19 impacts the susceptibility of these thrombi to thrombolytic treatments remain unknown, however. Objectives: We aimed to characterize AIS thrombi from COVID‐19 patients by immunohistology and to compare their response to thrombolysis to that of AIS thrombi from non‐COVID‐19 patients. Patients/Methods: For this monocentric cohort study, 14 thrombi from COVID‐19 AIS patients and 16 thrombi from non‐COVID‐19 patients, all recovered by endovascular therapy, were analyzed by immunohistology or subjected to ex vivo thrombolysis by tissue‐type plasminogen (tPA)/plasminogen. Results: COVID‐19 AIS thrombi were rich in neutrophils and contained NETs, but not spike protein. Thrombolysis assays revealed a mean resistance profile to tPA/plasminogen of COVID‐19 AIS thrombi similar to that of non‐COVID‐19 AIS thrombi. The addition of DNase 1 successfully improved thrombolysis by potentiating fibrinolysis irrespective of COVID‐19 status. Levels of neutrophil, NETs, and platelet markers in lysis supernatants were comparable between AIS thrombi from non‐COVID‐19 and COVID‐19 patients. Conclusions: These results show that COVID‐19 does not impact NETs content or worsen fibrinolysis resistance of AIS thrombi, a therapeutic hurdle that could be overcome by DNase 1 even in the context of SARS‐CoV‐2 infection.